Lantbruk i framtiden - Lorin, Stefan (2005)
The economic prerequisite to many farmers in Sweden after the EU membership and the new agriculture policy has generated large demands on the farm management. Until year 2004 you got a grant based on what you had produced and not on consumer demand. In 2005 a new economic aid (Mid Term Revue) was introduced and the conditions has changed again. Due to this I have chosen to do a cost-benefit analysis on a case, to investigate if the present production is sustainable in the future. My conclusion is that the profitability is acceptable even if the farm has a high debt. But to make the production more profitable the products produced should be refined as much as possible at the farm, to get maximum economic return. The discount on slaughter pigs is not satisfied but the pig production gives a higher economic return on the own produced serials. One reason to the high profit on serials is due to efficiency improvement and high utilization of most machinery used, this gives a cost between 1700 – 2600 SEK/ha for the equipment. The phosphorus and potassium needs are provided by pig-manure and this improves the profit of the pig-production. I have also investigated which economic prerequisites the farm has to refine the products produced, and if there excists any other crop that are more profitable to include in the crop rotation. I have chosen to investigate two crops, production of oil seed rape to refine it to rape oil and hempplants for heating. My conclusion is that Swedish agriculture has a future, but it reqvest high demands on business managers and employees. You must always be aware of the costs because it is hard to affect the income. Small changes in the interest, economic return and production costs can make the different.